Will restricting proprietary trading and stricter derivatives regulation make the US financial system more stable? - Kregel, Jan (PSL Quarterly Review, 2011)
Two of the major provisions of the Dodd‐Frank Wall Street Reform and Consumer Protection Act, passed into law on July 21 2010, aim to reduce speculation with financial institutions own funds using highly leveraged derivatives. The so‐called “Volcker rule” limits the ability to trade as principal in what is known as “proprietary trading” and the Lincoln Amendment or the “push out” rule limits derivatives dealing for regulated, insured banks. A complement to the Lincoln amendment requires that all over the counter derivatives be cleared through official mechanisms and traded on regulated exchanges similar to those used for commodities. JEL Codes: E11, G01, B50, H12